2019
DOI: 10.1116/1.5085051
|View full text |Cite
|
Sign up to set email alerts
|

Penetration depth variation in atomic layer deposition on multiwalled carbon nanotube forests

Abstract: Atomic layer deposition (ALD) of Al2O3 on tall multiwalled carbon nanotube forests shows concentration variation with depth in discrete steps. While ALD is capable of extremely conformal deposition in high aspect ratio structures, decreasing penetration depth has been observed over multiple thermal ALD cycles on 1.3 mm tall multiwalled carbon nanotube forests. Scanning electron microscopy imaging with energy dispersive x-ray spectroscopy elemental analysis shows steps of decreasing intensity corresponding to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Kane et al have shown the positive effect of longer pulse length, which is very significant for the high temperature reported by them (∼330 °C) . However, at a temperature of 200 °C, a TMA/H 2 O pulse length of 15 ms was found not to be a limiting factor, as pulses of 150 and 200 ms led to worse suffocation depth on the pristine sample and greater inhomogeneity of composite materials (S-19 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Kane et al have shown the positive effect of longer pulse length, which is very significant for the high temperature reported by them (∼330 °C) . However, at a temperature of 200 °C, a TMA/H 2 O pulse length of 15 ms was found not to be a limiting factor, as pulses of 150 and 200 ms led to worse suffocation depth on the pristine sample and greater inhomogeneity of composite materials (S-19 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
“…The enhanced temperature increased the kinetic energies of precursors, enabling a greater diffusion coefficient and thus deeper penetration. Even though reported as having larger penetration depth, higher ALD temperatures were not explored, in efforts to prevent any effects on the CNT, as temperature above 300 °C are reported as annealing . Homogeneous 350 μm-thick nanocomposites are more than enough for most electrical applications. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the challenge of the ALD process in high aspect ratio and nanoporous materials 17,17,[26][27][28] , research has been mostly focused on the mesoporous MOF NU-1000. Indeed, the first example was reported in 2013, 29 and since then almost all studies have focused on Zr6-based frameworks, among which only NU-1000 and UiO-66 were studied in depth 11,12,[30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…In the field of MOFs, ALD was first employed to grow a metal oxide layer on substrates in order to facilitate MOF growth. Later, it was implemented for PSM; in all the studies, a metallic precursor and H 2 O were used successively to grow metal oxide/hydroxide clusters inside the porous framework or on top of the MOF crystallites. Because of the challenge of the ALD process in high-aspect-ratio and nanoporous materials, ,, research has been mostly focused on the mesoporous MOF NU-1000. Indeed, the first example was reported in 2013, and since then, almost all studies have focused on Zr 6 -based frameworks, among which only NU-1000 and UiO-66 were studied in depth. ,, Both are formed by Zr 6 O 4 (OH) 4 nodes with reactive OH groups; therefore, ALD reactions occur at the inorganic unit.…”
Section: Introductionmentioning
confidence: 99%